Influence of Argon/oxygen Ratio on Linear and Nonlinear Optical Properties of Copper Doped ZnO Films - Xing WEN; Yue HAN; Cheng-Bao YAO; Ke-Xin ZHANG; Jin LI; Wen-Jun SUN (Medžiagotyra, 2019)
Copper (Cu)-doped ZnO (CZO) films were grown by simultaneous direct current and radio frequency magnetron sputtering technique under the situation of different gas flow rates of Ar: O2 (1:1, 2:1 and 1:0). The X-ray diffraction patterns revealed the naturally polycrystalline ZnO films with the predominant reflection (002) peak, which referred to the hexagonal wurtzite structure toward c-axis. The elemental composition of thin films was analyzed by energy dispersive spectroscopy (EDS). The Cu concentrations in thin films increased with Ar ratio of up to 1:0. The EDS spectra of three kinds of elements indicate that Cu-doping has obvious and sophisticated effect on the chemical state of oxygen, but less effect on those of copper and zinc. Furthermore, the nonlinear absorption of CZO films was investigated by the way of Z-scan technique. These films demonstrated good nonlinear absorption behavior for the different gas flow rates of Ar: O2.